Análise cinemática de uma plataforma de stewart por meio da modelagem de dinâmica de multicorpos - Silva, Lucas Leronardo Lopes (Universidade Federal Rural do Semi-Árido, 2019)
This present study is a kinematic analysis, process that aims to study the movements of a specific mechanism, with purpose of collect data of yours positions, velocities and accelerations in an instant. This was done by means of a bibliography review of articles, dissertations, books, monographs, theses and others materials, in order to get information and data that may be judged needed and sufficient, for the study of specify mechanism, Stewart platform. The Stewart platforms is a parallel mechanism compost for two bases and six arms, with multiplies applications in motion simulators. The realization of kinematic analysis for the study of actions of positions, velocities and accelerations of same, this method has been implemented with a helper software, MATLAB. Soon, after a quickly show of concepts, that include knowledge about mechanisms kinematic analysis and the used software MATLAB, will be explained all the steps for the realization of kinematics analysis. Therefore, with obtained results, the selected project of Stewart platform it was successful, making the proposed moves without significantly error and obtain a satisfactory data set for future analysis and implementations.
Monografia
Keywords: Plataforma de Stewart; Cinemática; MATLAB; Stewart platform; Kinematic; MATLAB; ENGENHARIAS::ENGENHARIA MECANICA